Blood-brain barrier disruption mediates the association between cerebral small vessel disease and clinical outcome after stroke: a secondary analysis of the Lesion Evolution in Stroke and Ischemia on Neuroimaging study - Okine, Derrick N.; Kern, Kyle C.; Luby, Marie; Latour, Lawrence L.; Gottesman, Rebecca F. (Frontiers in Stroke, 2024)
Introduction: White matter hyperintensities (WMH) in patients presenting with acute ischemic stroke are associated with worse clinical outcomes, but the mechanisms underlying this association are unclear. The purpose of this study was to determine whether blood-brain barrier (BBB) disruption, detected as the hyperintense acute reperfusion marker (HARM) on post-gadolinium follow-up FLAIR MRI, is associated with WMH and mediates the association between WMH and stroke outcomes. Methods: This is a secondary analysis of the LESION study, where patients with suspected acute ischemic stroke who were candidates for acute stroke intervention or had a baseline NIHSS ≥ 4 underwent serial multimodal MRI within 24 hours of last-known-well time, and again at 2 or 24 hours. WMH were visually graded on baseline FLAIR for presence and severity (minor or moderate-severe). HARM was evaluated on post-gadolinium FLAIR for presence and severity (minor, severe focal or severe diffuse). Using binomial and multinomial logistic regression, we tested whether WMH grade was associated with presence or severity of HARM, covarying for demographics, vascular risk factors, and stroke characteristics in sequential models. Finally, we used structural equation models to test the mediation effects of severe HARM on the association between WMH and stroke outcomes, including discharge NIHSS, hemorrhagic transformation, and 90-day modified Rankin scale. Results: For 213 stroke patients (mean age 70 years, 54% female), higher WMH grade was associated with increased risk for severe diffuse HARM (OR:3.37, 95% CI: 1.45-7.81), although not after adjusting for vascular risk factors or stroke characteristics. In our univariate model, severe HARM had a partial mediating effect between WMH and discharge NIHSS, explaining 23% of the association. Discussion: These findings suggest a possible association between severe diffuse HARM and WMH severity. The relationship between WMH severity and early stroke outcome may be mediated by blood-brain barrier disruption.